Women made visible: a different perspective on the history of the Institute of Tropical Medicine in Portugal, 1943-1966 - João Lourenço Monteiro (História, Ciências, Saúde: Manguinhos, 2021)
Abstract This work focuses on the scientific research conducted by women at Portugal’s Institute of Tropical Medicine between 1943 and 1966. The Institute’s scientific journal documents the participation of women in tropical medicine during this period. Their publications addressed a variety of subjects and resulted from research carried out in the metropolis as well as Portugal’s overseas colonies. Most of the articles written by these women were are co-authored by their male colleagues, reflecting the incorporation of female researchers into scientific networks already established by men. This work in progress provides a starting point to lend visibility to a group of scientific actors who are practically absent from the historiography of tropical medicine.